1978
DOI: 10.1017/s0033291700018833
|View full text |Cite
|
Sign up to set email alerts
|

Conjoint marital therapy: a controlled outcome study

Abstract: SynopsisForty-two couples with marital problems were randomly allocated to conjoint therapy of (i) a directive, (ii) an interpretative or (iii) a supportive (control) type. Self and independent assessment at the end of treatment showed the directive significantly superior to the control procedure on several measures. This superiority was maintained to 18 months' follow-up, when the interpretative procedure also showed some superiority over the control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(57 citation statements)
references
References 19 publications
0
57
0
Order By: Relevance
“…For a combined sample of 200 Clinical and Nonclinical couples, Eidelson & Epstein (1982) report correlations between the RBI and the LockeWallace Marital Adjustment Scale (Locke & Wallace, 1959) of -.57, -.24, -.38 and -.25 for the "Disagreement is Destructive", "Mind-reading is Expected", "Partners Cannot Change" and "The Sexes are Different" subscales respectively. Emmelkamp et al (1987) report correlations between the Maudley Marital Questionnaire (Crowe, 1978) and the RBI subscales of .31/ .38 for the Disagreement subscale (for non-distressed and distressed couples), .04/.21 for Mind-reading, .22/.43 for Change and .19/.05 for the Sex Differences subscales. Recent reviews using a greater diversity of relationship belief and quality indices have suggested that the link between these beliefs and relationship quality are only moderate and may be mediated by the strength of relationship expectations (Karney et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For a combined sample of 200 Clinical and Nonclinical couples, Eidelson & Epstein (1982) report correlations between the RBI and the LockeWallace Marital Adjustment Scale (Locke & Wallace, 1959) of -.57, -.24, -.38 and -.25 for the "Disagreement is Destructive", "Mind-reading is Expected", "Partners Cannot Change" and "The Sexes are Different" subscales respectively. Emmelkamp et al (1987) report correlations between the Maudley Marital Questionnaire (Crowe, 1978) and the RBI subscales of .31/ .38 for the Disagreement subscale (for non-distressed and distressed couples), .04/.21 for Mind-reading, .22/.43 for Change and .19/.05 for the Sex Differences subscales. Recent reviews using a greater diversity of relationship belief and quality indices have suggested that the link between these beliefs and relationship quality are only moderate and may be mediated by the strength of relationship expectations (Karney et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We used the Maudsley Marital Questionnaire (MMQ; Crowe, 1978), Dutch adaptation (Arrindell, Boelens, & Lambert, 1983), to assess marital dissatisfaction (possible range: 0-80). Higher scores represent greater dissatisfaction.…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…Participants in these studies included self-referrals, referrals from community agencies, and couples recruited from advertisements or from screening parents of chronically-ill children. The primary measure of relationship distress in 14 studies was the Dyadic adjustment scale (Spanier, 1976); in 3, was the Maudsley Marital Questionnaire (Crowe, 1978); in 2, was the Marital Adjustment Scale (Locke & Wallace, 1959) and in 1, was the General Happiness Rating Scale (Terman, 1938). Dropout rates from the 13 BCT studies ranged from 0% to 39% with a mean of 12%.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%